The Formation and the Development of the Újházhely Residential Area in Hajdúnánás - Kutasi, Imre (Ethnographica et Folkloristica Carpathica, 2024)
In Hungary, it was the land reform of 1945 which caused one of the most significant changes in the land policy. This measure, aimed at allocating land to landless peasants, utilized a total of 3,220,000 ha, which were distributed among 642,000 beneficiaries. As a result, each beneficiary received an average of 2,9 ha of agricultural land, on which they could make a living, albeit under difficult conditions. Historical research has examined this phenomenon, allowing us to understand its effects on Hungarian agriculture and the peasants. It is a less known fact, that not only agricultural lands but also – according to the previous works – in approximately 2800 settlements 300,000–450,000 building sites were distributed. As a result, new farmstead centers, settlements and residential areas emerged. This topic is a less researched area of the history of the Hungarian countryside, even though it caused many changes in the society of these settlements. To provide a more comprehensive understanding of these phenomena, the aim of my presentation is to illustrate this process using the example of Hajdúnánás, a small town located in northern Hajdú-Bihar County. This includes the occupation of agricultural lands, payment of expenses (such as contributions and redemption fees), the distribution of building sites, and the settlement and development of the Újházhely residential area. For this research, I utilized historical sources including electoral registers, house tax records, maps, statistical data, archival sources, legal documents, and interviews.